Making markets for structured mortgage derivatives - Oldfield, G (Journal of Financial Economics, 2000)
This paper distinguishes between securitization, in which simple pass-through instruments are created, and structuring, in which mortgages derivative claims are created. The point is to explain how structuring a transaction brings value to a deal's underwriter. Briefly, an underwriter must defeat arbitrage between pass-throughs and derivatives. The potential for market segmentation and price discrimination by the underwriter is used to analyze the structuring process. In the course of the analysis, the legal rules for trusts, the algebraic rules for structuring, and the limits on permissible price discrimination are discussed. Results for an actual transaction illustrate the important features of the analysis.